Distribusi Temporal Aves dan Kualitas Perairan di Daerah Persawahan Jempong Barat, Kota Mataram - Muhamad Zulhariadi; Riri Septia Hariyani; Baiq Nita Diniati; Ihdal Husnayain (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
Rice field areas that are the habitat of several types of water birds that make up the ecosystem continue to decline in several urban areas including Mataram City. This study aims to conduct routine observations every year on the diversity of birds that inhabit the rice field areas of Mataram City and its surroundings. This study aims to calculate the temporal distribution of birds in the Jempong Barat Rice Field Area, Mataram City along with its environmental parameters. This type of research is descriptive exploratory with a roaming method to observe birds and measure environmental parameters of water quality in rice fields. The results of the study showed that there were 7 species of rice field birds and 3 of them were aquatic birds (wetland). The time most often found birds was in the morning. The Bird Diversity Index is in the medium category (H '= 1.68) and the quality of rice field waters generally meets water quality standards.